Taking a Bite: Food Business Preservation in Union Square, Somerville. - Flanary, Michael; Mlsna, Ivy; Johnson, Stephanie.; Xu, Wencong. (Tufts University. Tisch Library., 2018)
2017 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Somerville Arts Council Nibble.